Mandarin speech reconstruction from surface electromyography based on generative adversarial networks - Fengji Li; Fei Shen; Ding Ma; Jie Zhou; Li Wang; Fan Fan; Tao Liu; Xiaohong Chen; Tomoki Toda; Haijun Niu (Medicine in Novel Technology and Devices)
The loss of speech function due to conditions such as laryngectomy and vocal cord paralysis significantly impacts the quality of life for patients. Achieving effective communication for these patients is a goal pursued by researchers. This study primarily explores a method for reconstructing Mandarin speech based on voice-related neck and facial surface electromyography (sEMG). Neck and facial sEMG signals and speech waveform were synchronously collected during normal speech production. A speech reconstruction model for Mandarin speech, based on multi-scale feature extraction from EMG and a generative adversarial network (GAN), was developed. Both subjective and objective evaluations were conducted to assess the speech reconstruction performance of the model. The evaluation results indicate that the model effectively reconstructs speech from neck and facial sEMG signals. The reconstructed speech closely matches the original in terms of spectrogram and fundamental frequency, with mel-cepstrum distortion of 8.45 ​dB, log F0 RMSE of 0.40, F0 correlation coefficient of 0.71 and F0 voiced/unvoiced estimation accuracy of 0.80. The character error rate of the reconstructed speech is 0.32, while the tone error rate is 0.26. The subjective listening test results show that the naturalness of the reconstructed speech is acceptable, with a mean opinion score greater than 3. This study demonstrates the potential of deep learning techniques in effectively reconstructing Mandarin speech from sEMG.